Sediment and nutrient deposition in different riparian forests and floods of the Middle Paraná River - Marchetti, Zuleica Yael (2019)
Sedimentation processes are important to the dynamics of lowland fluvial systems and depend on the characteristics of floods and of riparian ecosystems. The few known studies for the Paraná River system analyzed only summer floods without considering the context in which the sedimentation occurred. This study focuses on sedimentation in three riparian forests during one summer and two winter floods of the Paraná River, quantifying the amount of deposited sediments, determining their texture, and measuring the associated quantities of Total Phosphorous (TP) and Total Nitrogen (TN). This study takes into account the elevations, floristic attributes, and geomorphologic context of the three forests, as well as water and sediment transport during floods. Differences in the floods’ water discharge, wash load, and duration determined differences in the total amounts of drained water and mobilized sediments. The amount of sediments ranged from 0 to 510 kg m‐2 in the different floods and riparian forests studied. The texture was statistically different between the two winter floods, and between some riparian forests. The analysis of nutrients showed that 1 to 4919 kg ha‐1 of TP and 4.2 to 1152 kg ha‐1 of TN were deposited during the three floods in all forest types. Our results show that the amounts from winter floods can be as important as those from summer floods. These results provide insight not only into the importance of winter floods in the deposition processes, but also into the role of both types of floods as natural instruments of fertilization for floodplain‐river ecosystems.